Morpho-molecular diversity of Bipolaris oryzae causing brown spot of paddy - KUMAR, ATUL; SOLANKI, ISHWAR SINGH; AKHTAR, JAMEEL; GUPTA, VISHAL (The Indian Journal of Agricultural Sciences, 2016)
Brown spot of paddy caused by Bipolaris oryzae is a threat to paddy cultivation across the globe. An extensive survey was conducted during kharif seasons of 2012, 2013 and 2014 and 116 isolates of B. oryzae were isolated from the diseased specimens collected from different geographical locations of India representing major rice growing regions. The isolates were charactaerized for morphological traits like colony characters, colony diameter, and sporulation. On the basis of colony morphology and growth pattern on PDA, these isolates were grouped into 8 different categories. Based on colony diameter, all these isolates were grouped into 3 different categories of slow, moderate and fast growing isolates. Maximum sporulation was observed in isolates from Bihar and Jharkhand while the least sporulation was seen in isolates from Gujarat. The molecular characterization carried out on 20 representative isolates using random apmlified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) revealed variability in the isolates. These differences were also observed when cluster analysis was carried out. Out of 20 RAPD and 20 ISSR primers, 5 RAPD and ISSR primers each gave very nice reproducible banding patterns. Polymorphism ranged between 54.0-100% in RAPD markers while it was from 49.2-100% with ISSR markers. This is the first study in our country wherein isolates representing all major rice growing areas of the country has been taken into consideration for variability study and it was observed both by morphological and molecular methods.